Long-term evaluation of soft tissue profile changes induced by Herbst appliance followed by fixed appliances (Research, Society and Development, 2022)
The present investigation aimed to evaluate, by cephalometric analysis, the soft tissue profile changes in adolescents with Class II Division 1 malocclusion, treated with Herbst appliance (Stage I) and fixed appliances (Stage II), followed-up for an average of 4 years (Stage III). The adolescents were divided into two groups: treated group (TG) - 33 adolescents with Class II malocclusions (17 boys and 16 girls) consecutively treated with Herbst appliance and fixed appliances; control group (CG) - 28 adolescents (13 boys and 15 girls) with untreated Class II malocclusions. Lateral cephalograms were obtained immediately before (T1) and after (T2) Herbst treatment, after fixed appliances (T3), and on average, 4 years after orthodontic treatment. Intergroup comparison was evaluated by t or Mann-Whitney tests. The TG was evaluated by analysis of variance followed by Tukey test or Friedman test followed by Dunn’s test. Compared to the CG, the TG showed significant favorable changes at Stage I: decrease in facial convexity, upper lip retrusion, lower lip protrusion, improvement of soft tissue pogonion and increase in mentolabial angle. The total posttreatment period (T2-T4) of the TG showed: increase in H line-Prn, and upper and lower lips retrusion, while the others variables remained stable. This study suggests that Herbst therapy improved features of soft tissue facial profile, which were maintained after fixed appliances and for an average of 4 years posttreatment, although the convex facial characteristic has prevailed.